Impact of Ethics in Electronic Commerce - Nimo J R, Ashlin; Kumar R, Ganesh (International Journal of Engineering and Technology, 2018)
Internet was a tool to search information and communicate with each other during the early days of its emergence. Now, we can state that Internet has been commercialized (Electronic Commerce emerged). Nowadays, all businesses are taking place online. The online system gives a lot of merits to both customers and business organizations. But the demerits of electronic commerce are unavoidable. The major drawback of e-commerce is its ethical issue. These ethics issues are because of irresponsible parties who are a threat to both customers and business organizations. The online platform is not the same as traditional brick and mortar stores. Is it necessary to consider ethical issues in business? If so, whether steps should be taken to implement and address ethical issues.Â